AB0998 TRABECULAR BONE SCORE IN PEDIATRICS, IS IT USEFUL?. (13th June 2020) - Magallares López, B. P.; Park, H.; Cerda, D.; Betancourt, J.; Fraga, G.; Boronat, S.; Herrera, S.; Marín, A. M.; Gich, I.; Malouf, J.; Casademont, J.; García-Guillén, A.; et al.
Abstract : Background: Bone fragility depends not only on bone mineral density (BMD), but also on bone microarchitecture. In adults, Trabecular Bone Score (TBS) is being used as an indirect marker of bone microarchitecture It is a software that applicated to the vertebral image obtained by conventional densitometry, informs about the thickness of the trabeculae, the trabecular connectivity and the space between them. A high score indicates a better bone microstructure. In adults, a TBS equal to or greater than 1, 350 is considered to represent a normal microarchitecture Objectives: To evaluate the usefulness of TBS in pediatric population with risk factors for Low Bone Mass (LBM) Methods: TBS was assessed by analyzing vertebral densitometries performed on patients from 4 to 20 years of age, assessed in the pediatric rheumatology office of our hospital for presenting risk factors for LBM, consecutively from 2016 until 2018 Data were compared with normal pediatric population Results: Data from 83 patients are shown, with an average age of 11.2 years, 62% female, 80% Caucasian The main risk factors for LBM were (%): Insufficient calcium intake (84, 5), medications with osteopenizing potential (31), corticosteroids (39), sedentary lifestyle (13, 6), fractures of long or vertebral bones (12, 6) and hypovitaminosis D (8, 1) Conclusion: TBS was lower in the patients with LBM by whole body Z score, but not in those with LBM by spine Z score. We observed a decrease in TBS in adolescence, not corresponding with a decrease in BMD, and that should not be interpreted as a pathological finding Similar results have been described in other pediatric populations (1, 2), but larger studies are needed to evaluate this phenomenon. We hypothesize that it may be due to a higher rate of growth in adolescence, with a lower rate of calcium apposition into the osteoid material References: [1]Del Rio DS, Winthenrieth R. BONE MICROARCHITECTURE (TBS) AND BONE MASS DEVELOPMENT DURING CHILDHOOD AND ADOLESCENCE IN A SPANISH POPULATION GROUP. . WCO-IOF-ESCEO; Seville2014. [2]Shawwa K, Arabi A, Nabulsi M, et al. Predictors of trabecular bone score in school children. Osteoporosis international: a journal established as result of cooperation between the European Foundation for Osteoporosis and the National Osteoporosis Foundation of the USA. 2016;27(2):703-10. Disclosure of Interests: None declared